Failure and Success in Modern Drug Discovery: Guiding Principles in the Establishment of High Probability of Success Drug Discovery Organizations - Rishton, G. M. (Medicinal Chemistry, 2005)
The pharmaceutical industry currently suffers unsustainably high program failure rates despite our best efforts to implement drug design methods and to develop high throughput biochemical screening technologies over the past 20 years. While much of this failure is rationalized to be due to uncontrollable late stage drug development issues and clinical events, it has become increasingly clear that the choices we make in early drug discovery are vital to the ultimate failure or success outcomes of our drug discovery programs. The judicious selection of high probability of success therapeutic modalities, the rigorous determination of leadlikeness and druglikeness, and the all-important selection of high probability of success enzyme and receptor targets are the vital drivers of failure and success in small molecule drug discovery as it is performed in the age of biochemical screening. Consideration of these guiding principles will improve our chances of success in drug discovery, and increase our ability to address unmet medical need in the future.
Keywords: success in drug discovery